2017
DOI: 10.1038/s41598-017-14606-3
|View full text |Cite
|
Sign up to set email alerts
|

A missense mutation in SLC26A3 is associated with human male subfertility and impaired activation of CFTR

Abstract: Chloride absorption and bicarbonate excretion through exchange by the solute carrier family 26 member 3 (SLC26A3) and cystic fibrosis transmembrane conductance regulator (CFTR) are crucial for many tissues including sperm and epithelia of the male reproductive tract. Homozygous SLC26A3 mutations cause congenital chloride diarrhea with male subfertility, while homozygous CFTR mutations cause cystic fibrosis with male infertility. Some homozygous or heterozygous CFTR mutations only manifest as male infertility. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 66 publications
0
15
0
Order By: Relevance
“…As observed in the context of the sperm cells, although present within the epididymal ductus, SLC26A6 function seems to be dispensable for epididymal cytoarchitecture and functionality. Lastly, SLC26A8 protein was found absent from the epididymal tract (Kujala et al, 2007; Wedenoja et al, 2017; El Khouri et al, 2018) and rationally no epididymal phenotype was observed in the knock-out mice (Touré et al, 2007).…”
Section: Slc26 Proteins In Sperm Function and Male Fertilitymentioning
confidence: 85%
See 1 more Smart Citation
“…As observed in the context of the sperm cells, although present within the epididymal ductus, SLC26A6 function seems to be dispensable for epididymal cytoarchitecture and functionality. Lastly, SLC26A8 protein was found absent from the epididymal tract (Kujala et al, 2007; Wedenoja et al, 2017; El Khouri et al, 2018) and rationally no epididymal phenotype was observed in the knock-out mice (Touré et al, 2007).…”
Section: Slc26 Proteins In Sperm Function and Male Fertilitymentioning
confidence: 85%
“…Among those, the CatSPER channel (cation channel sperm associated) is a multiprotein complex, which exclusively locates to the plasma membrane of the principal piece in human and mouse sperm flagellum, and mediates Ca 2+ influxes (Figure 4; see review Singh and Rajender, 2015). In consistence with their restricted expression and function during capacitation, mutations in some genes encoding for some of the above ionic transporters (CatSPER1, CatSPER2, SLC26A3, and SLC26A8) were associated with male infertility due to asthenozoospermia, a pathology defined by reduced or absence of sperm motility (Hildebrand et al, 2010; Ray et al, 2017; Wedenoja et al, 2017).…”
Section: Sperm Capacitation In the Female Genital Tractmentioning
confidence: 99%
“…Renal insufficiency is observed in ~25% of CLD subjects, although this likely results from delayed diagnosis and consequent chronic volume and salt depletion (15). SLC26A3 mutations are also associated with male subfertility, although available evidence suggests that impaired SLC26A3-CFTR interaction and consequent impaired CFTR activity are responsible (43). In general, with appropriate salt-replacement therapy, the long-term health in CLD is good, suggesting the absence of significant tumor and nongastrointestinal problems with SLC26A3 mutation (40).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, human mutations within the STAS domain of many SLC26 family members can cause diseases (Rapp et al, 2017). For example, a specific STAS domain mutation in SLC26A3, which is associated with male subfertility, impairs SLC26A3 interaction with CFTR (Wedenoja et al, 2017). Another study showed that a specific SLC26A2-STAS mutation associated with the skeletal disease, diastrophic dysplasia, impairs SLC26A2 trafficking to the plasma membrane (Rapp et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…This underscores the quintessential role that STAS plays in controlling SLC26 function and expression (Ko et al, 2004;Dorwart et al, 2008;Ohana et al, 2013;Geertsma et al, 2015). Remarkably, numerous human mutations were identified in the STAS domain of different SLC26 transporters causing many diseases including, diastrophic dysplasia (SLC26A2) (Cai et al, 2015), congenital chloride diarrhea (SLC26A3) (Dorwart et al, 2008), Pendred syndrome (SLC26A4) (Everett et al, 1997), and infertility (SLC26A8/A3) (Dirami et al, 2013;Rapp et al, 2017;Wedenoja et al, 2017). Notably, the Slc26a6/Nadc-1 complex was shown to control blood pressure by regulating succinate reabsorption at the proximal tubule, which, in turn, regulates the reninangiotensin system (Khamaysi et al, 2019).…”
Section: Introductionmentioning
confidence: 89%